Pemanfaatan Ekstrak Etanol Kelopak Bunga Rosela Untuk Pembuatan Kertas Indikator Asam-Basa Alternatif - Kusumah, Ine Yuliana Sari; , Triastuti Rahayu, S.Si, M.Si (2016)
Acid-base indicators are an important tool in a variety of experiments in science classes. From previous research paper has been created acid-base indicator of hibiscus extracts from family Malvaceae. Therefore, the aim of this study was to determine whether the distilled water and ethanol extracts of petals Rosela of familia Malvaceae which also can be used as the base material of paper making acid-base indicators. This study used an experimental method with a completely randomized design (CRD) with two factors, namely treatments used solvent type (B) and long soaking filter paper into Roselle calyx extract (A). Results of sensory test indicator paper petals Roselle extract, paper changes the color pink on a strong acid and a weak acid, light green color on a strong base and a green jade in a weak alkaline solution. The change signifies extract Rosella flower petals can be used as materials for acid-base indicator paper.